Análise da vigilância de infecção pós-alta de pacientes cirúrgicos, sob a ótica dos cirurgiões - Luciene de Souza Moreira Jota (2011)
Surgical site infection (SSI) has a considerable impact on morbidity and mortality, through raising costs due to time spent in the hospital and receiving treatment. It is among the health service related infections most possible to prevent, justifying the efforts in trying to reduce it. Studies demonstrate that active vigilance, with feedback rates to the surgeons, could reduce incidence by 30% to 40%. Vigilance after discharge is the major challenge in the face of reduced post-operation time spent in the hospital these days. There are various post-discharge methods and none of them is universally accepted as the best. This descriptive, observational, non-experimental study used the combination method known as methodological triangulation, which integrated qualitative and quantitative research. The data collection technique was the combination of questionnaire and semi-structured interviews with 60 surgeons from a variety of surgical fields in a private hospital in Belo Horizonte. The descriptive analysis of the questionnaire results allowed us to understand the outgoing surgery patient routine, the process of using the passive vigilance method (questionnaire-card) and the conduct of surgeons in the light of Centers for Disease Control and Prevention (CDC) criteria and diagnostics. On the basis of interview content analysis, four categories were defined: influence of the interpersonal factor; influence of socio-economic and geographical factors; influence of institutional and operational factors; and benefits of post-discharge infection control, with the aim of analyzing the implications of these factors as facilitators or inhibitors in the control of post-discharge infection and identifying post-discharge infection control benefits from the surgeons point of view. Results show that the majority of surgeons monitor all post-discharge cases through the call back scheduled in the out-patient clinic, but there is disbelief among them in relation to the questionnaire-card and the use of diagnostic criteria for non-standardized SSI, whereby the need to strengthen relations between surgeons and the infection control services is recognized. This study identified the points that make the control of post-discharge infection difficult, such as the degree of understanding, convenience and comfort of the patient; their financial and geographical situation; the limited integration between the health services; surgeon work overload; financial devaluation by the out-patient/consultative service, and the emphasis on pre and intra-surgery. There are many challenges to be overcome in order to minimize conflicts of interest but, as well as the the questionnaire card method already used, opinions indicate the usefulness of specific outpatient care for outgoing surgery patients and the possible benefits of Hospital Infection Control Service (SCIH) participation in this practice.